Temporal shape error concealment by global motion compensation with local refinement - Soares, Luis Ducla (IEEE transactions on image processing : a publication of the IEEE Signal Processing Society, 2006)
This paper presents an original temporal shape error concealment technique based on a combination of global and local motion compensation. For this technique, which is especially useful for object-based video applications in error-prone environments (e.g., mobile networks), it is assumed that the shape of the corrupted object at hand is in the form of a binary alpha plane and some of the shape data is missing due to channel errors. To conceal the corrupted shape, the decoder first assumes that a global motion model can describe the shape changes in consecutive time instants. This way, based on locally estimated global motion parameters, the decoder attempts to conceal the corrupted alpha plane by global motion compensating the shape data from the previous time instant. Afterwards, since a global motion model cannot perfectly describe all alpha plane changes, a local motion refinement is applied to improve the concealment in areas of the object with significant local motion